2005
DOI: 10.1179/174328105x48179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Na2O additions on thermal conductivities of CaO–SiO2slags

Abstract: Thermal conductivities of Na 2 O-CaO-SiO 2 slags have been determined using the non-stationary hot wire method over a wide temperature range between room temperature and 1773 K, to propose a prediction equation for the thermal conductivities of this slag system. Samples used were xNa 2 O-yCaO-zSiO 2 (xzyzz5100 mol-%), where 5,x,40 mol-% and 10,y,40 mol-%. With increasing temperature up to glass transition temperatures, the thermal conductivities of the samples increased and then decreased even beyond liquidus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 5 publications
4
26
0
Order By: Relevance
“…3,4) In this sense, studies pertaining to the relationship between the structure and physical properties of molten oxides have been carried out by a number of researchers with the intent to better design and optimize mold flux systems. [5][6][7][8][9][10][11][12][13] Because of the poor application of the additive rule, 14) and anomalous behavior in alkali/alkali earth oxide bearing systems, 15,16) the effect of boron oxide in mold flux systems has been given particular attention. [11][12][13][17][18][19] Wang et al 19) reported that the addition of B 2 O 3 leads to an increase number of [BO 4 ] tetrahedral units, which play an important role as network forming oxides in CaO-SiO 2 -B 2 O 3 -TiO 2 slag systems.…”
Section: Introductionmentioning
confidence: 99%
“…3,4) In this sense, studies pertaining to the relationship between the structure and physical properties of molten oxides have been carried out by a number of researchers with the intent to better design and optimize mold flux systems. [5][6][7][8][9][10][11][12][13] Because of the poor application of the additive rule, 14) and anomalous behavior in alkali/alkali earth oxide bearing systems, 15,16) the effect of boron oxide in mold flux systems has been given particular attention. [11][12][13][17][18][19] Wang et al 19) reported that the addition of B 2 O 3 leads to an increase number of [BO 4 ] tetrahedral units, which play an important role as network forming oxides in CaO-SiO 2 -B 2 O 3 -TiO 2 slag systems.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, wavelength range of 1-6 mm is emphasised on account of the characteristic of continuous casting process, actually, absorption spectrum of transition elements always expand to near ultraviolet band and infrared band, the wavelength range is 200-25000 nm. 23 S. Ozawa and M. Susa 24 and Susa et al 25 investigated the thermal conductivities of Na 2 O-CaO-SiO 2 and CaO-SiO 2 -Al 2 O 3 slag and found it increases with increasing temperature up to glass transition temperatures and then decrease even beyond liquidus temperatures. Cho et al studied the effect of the temperature on the radiative heat transfer properties of the mould fluxes and showed that there is little change in the structure of all the mould fluxes and not much difference in transmittance.…”
Section: Resultsmentioning
confidence: 99%
“…However, above the Debye temperature, owing to the approximately constant specific heat capacity (C) and mean particle velocity (v), the thermal conductivity of the oxide system decreases with increasing temperature as a result of the decrease in the phonon mean free path of collision (l), which is proportional to the inverse of the temperature (1/T). [25][26][27][28][29]31] Hence, it can be inferred that thermal conductivity reaches the maximum value around the Debye temperature, and then it decreases with higher temperatures. Therefore, identifying the Debye temperature in the oxide system is essential to evaluate the temperature at which thermal conductivity shows the maximum and to determine which variables mainly affect the thermal conductivity at the given temperature.…”
Section: Consideration Of One-dimensional Debye Temperature (θ D1 )mentioning
confidence: 98%
“…Although understanding the thermal conductivity of the molten oxide is also important for the thermal processing of the glass [22], the thermal conductivity measurement in the molten oxide system has been limited because of the large convection and the radiation effects [23]. However, owing to the several modifications of the non-steady state method, the thermal conductivity has been successfully measured in the molten oxide system over the last few decades [24][25][26][27][28][29][30][31][32][33]. Similar to other physical properties of the molten oxide system, the thermal conductivity is closely related to the network structure (i.e., silicate, aluminate, and borate structure.)…”
Section: Introductionmentioning
confidence: 99%